Interplay Between Air Travel, Genome Integrity, and COVID-19 Risk vis-a-vis Flight Crew - Toprani, Sneh M.; Scheibler, Christopher; Nagel, Zachary D. (Frontiers in Public Health, 2020)
During air travel, flight crew (flight attendants, pilots) can be exposed to numerous flight-related environmental DNA damaging agents that may be at the root of an excess risk of cancer and other diseases. This already complex mix of exposures is now joined by SARS-CoV-2, the virus that causes COVID-19. The complex exposures experienced during air travel present a challenge to public health research, but also provide an opportunity to consider new strategies for understanding and countering their health effects. In this article, we focus on threats to genomic integrity that occur during air travel and discuss how these threats and our ability to respond to them may influence the risk of SARS-CoV-2 infection and the development of range of severity of the symptoms. We also discuss how the virus itself may lead to compromised genome integrity. We argue that dauntingly complex public health problems, such as the challenge of protecting flight crew from COVID-19, must be met with interdisciplinary research teams that include epidemiologists, engineers, and mechanistic biologists.